Direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami region and preparation method thereof

By grinding coal slurry in the coal species in Hami area and adding surfactant and non-ferrous metal salts, combined with oxygen treatment, the dispersion and catalytic effect of the catalyst are improved, and the problem of insufficient catalytic effect under mild liquefaction conditions is solved, and efficient Direct liquefaction of coal reduces the cost of coal liquefaction plants.

CN119158586APending Publication Date: 2024-12-20CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411410267.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively catalyze the direct liquefaction of coal species in Hami area under mild liquefaction conditions, resulting in insufficient catalytic effect and increasing the investment and operation costs of coal direct liquefaction plants.

Method used

A method for preparing a direct coal liquefaction catalyst is adopted. By grinding coal slurry and adding surfactant, iron salt and non-ferrous metal salt, combined with oxygen treatment, the dispersion and catalytic effect of the catalyst are improved, which is suitable for mild liquefaction of coal species in Hami area.

Benefits of technology

It significantly improves the conversion rate and oil yield of coal species under mild liquefaction conditions in Hami area, reduces the investment and operation costs of coal direct liquefaction plants, and provides economic benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a direct coal liquefaction catalyst suitable for mild coal liquefaction in the Hami region and a preparation method thereof, and relates to the technical field of direct coal liquefaction. The method comprises the following steps: firstly, preparing coal slurry with a certain mass fraction, and grinding and finely crushing the coal slurry; adding a surfactant into the obtained coal slurry to disperse the coal slurry; sequentially adding ferric salt and ammonia water into the dispersed coal slurry to obtain a first mixed solution; blowing oxygen into the first mixed solution, and after a period of time, adding a non-ferrous metal salt solution to obtain a second mixed solution; and filtering the second mixed solution, collecting solids, and drying the solids to obtain the product. According to the method, the dispersity and the catalytic effect of the iron-based catalyst can be effectively improved, and the coal liquefaction performance of coal with the inert component proportion being smaller than 2% under the mild liquefaction condition can be improved on the premise that a small amount of non-ferrous metal is used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of direct coal liquefaction, and in particular to a direct coal liquefaction catalyst, a preparation method and application thereof. Background Art

[0002] Direct coal liquefaction refers to the process of converting coal into liquid fuel through hydrocracking under the action of hydrogen and catalyst. It is an important technical approach to efficiently and cleanly utilize coal resources to convert them into liquid oil products, and is also one of the important coal chemical technologies to ensure national energy security.

[0003] There are many factors that affect the direct liquefaction of coal, including the type and quality of coal, catalyst, reaction temperature, reaction pressure and reaction time. Among them, the common direct liquefaction conditions of coal have a reaction temperature of 440-455°C and a pressure of 19MPa in the reactor. Mild liquefaction conditions refer to the direct liquefaction of coal at a temperature lower than the reaction temperature, reaction pressure, or at the reaction temperature and pressure conditions. This not only places high demands on the quality of coal, but also on the catalyst for direct liquefaction of coal.

[0004] Most of the direct coal liquefaction catalysts mainly use iron-based catalysts, which are low-priced, have certain catalytic activity, and do not need to be recycled after a one-time reaction. Currently, the most common iron-based catalysts are iron-based catalysts made of natural or recycled materials such as red mud, pyrite, iron sulfide and iron oxide. This type of catalyst is low-priced and has a general catalytic effect. Synthetic iron sulfide and iron oxide catalysts have high catalytic activity due to their small catalyst particle size and good dispersibility.

[0005] Coal types with an inert group ratio of less than 2% (such as coal types in the Hami area) have high coal liquefaction reaction activity. Mild liquefaction technology, which reduces the investment in plant construction and operating costs of direct coal liquefaction by lowering the reaction temperature and pressure, has become a research focus. The catalytic effect of existing industrial catalysts, namely synthetic iron-based hydrated oxide catalysts, is not sufficient to support the efficient conversion of Hami coal under mild liquefaction conditions. Although the large-scale use of non-ferrous metal catalysts can improve the catalytic effect of industrial catalysts, the cost is relatively high. Therefore, the development of direct liquefaction catalysts suitable for coal types with an inert group ratio of less than 2% is a key technology in mild liquefaction technology. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in the Hami area, which can effectively improve the dispersibility and catalytic effect of iron-based catalysts. On the premise of using a small amount of non-ferrous metals, the coal liquefaction performance of coal with an inert group proportion of less than 2% under mild liquefaction conditions can be improved.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a coal direct liquefaction catalyst suitable for mild liquefaction of coal in Hami area, wherein the inert group of the coal accounts for less than 2%, and the preparation method comprises the following steps:

[0009] (1) Prepare a coal slurry with a certain mass fraction and grind it into fine powder;

[0010] (2) adding a surfactant to the coal slurry obtained in step (1) to disperse it;

[0011] (3) adding iron salt and ammonia water to the coal slurry dispersed in step (2) in sequence to obtain a first mixed solution;

[0012] (4) blowing oxygen into the first mixed solution, and after a period of time, adding a solution of a non-ferrous metal salt to obtain a second mixed solution;

[0013] (5) Filter the second mixed solution, collect the solid and dry it to obtain the product.

[0014] The above-mentioned method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area comprises the following steps: in step (1), coal powder is crushed and mixed with water to prepare coal slurry, wherein the mass fraction of the coal slurry is 20-80%; and the coal powder is ground in a ball mill to a size of 0.8-80 μm.

[0015] The above-mentioned method for preparing a coal direct liquefaction catalyst suitable for mild liquefaction of coal in Hami area, in step (2), the above-mentioned surfactant is an anionic surfactant, and the above-mentioned anionic surfactant is one or a mixture of several of alkylbenzene sulfonic acid, ammonium salt, naphthalene sulfonate, and lignin sulfonate.

[0016] The above-mentioned method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area, in step (2), the above-mentioned surfactant is sodium lignin sulfonate, and the addition amount of the above-mentioned sodium lignin sulfonate is 0.01-1% of the mass of the coal slurry obtained in step (1).

[0017] The above-mentioned method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area, in step (3), the concentration of the iron salt solution is 10-30wt%, and the concentration of the ammonia solution is 10-30wt%; the iron salt solution and ammonia water are fed in a mass ratio of 3-6:1; preferably, the iron salt in the above-mentioned iron salt solution is one or a mixture of divalent sulfate, trivalent sulfate, nitrate.

[0018] In the above-mentioned method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area, in step (4), the non-ferrous metal salt is one or a mixture of sulfates, nitrates and ammonium salts of molybdenum, nickel and tungsten.

[0019] The above-mentioned method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area, the addition amount of the above-mentioned non-ferrous metal salt is 1-5% of the mass of the iron salt; the volume ratio of oxygen to coal slurry in the first mixed liquid is 500-1000:1, and the time for blowing oxygen is ≥30 minutes.

[0020] In the above-mentioned method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area, in step (5), the drying temperature is 100-180° C., and the mass content of water in the catalyst obtained after drying is less than 2%.

[0021] Another object of the present invention is to provide a coal direct liquefaction catalyst suitable for mild liquefaction of coal in Hami area, which is prepared by the above-mentioned preparation method.

[0022] Compared with the prior art, the present invention brings the following beneficial technical effects:

[0023] (1) The coal direct liquefaction catalyst of the present invention has a simple process flow, good catalyst dispersion effect, and excellent catalytic effect. It is suitable for the coal direct liquefaction process of high-quality coal liquefaction coal in Hami area under mild liquefaction conditions, and has great economic benefits in reducing the investment, construction, and production and operation costs of coal direct liquefaction plants.

[0024] (2) The present invention can effectively improve the dispersibility and catalytic effect of iron-based catalysts, and improve the coal liquefaction performance of coal in the Hami area under mild liquefaction conditions while using a small amount of non-ferrous metals. DETAILED DESCRIPTION

[0025] The present invention proposes a coal direct liquefaction catalyst and a preparation method suitable for mild liquefaction of coal in Hami area. In order to make the advantages and technical solutions of the present invention clearer and more specific, the present invention is further described below in conjunction with specific embodiments.

[0026] The raw materials described in the present invention can be purchased through commercial channels.

[0027] The catalyst prepared by the present invention is particularly suitable for the direct liquefaction process of coal under mild liquefaction conditions of coal in the Hami area, and the inert group of coal in the Hami area accounts for less than 2%.

[0028] The present invention provides a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area and a preparation method thereof, which specifically comprises the following steps:

[0029] Step 1: prepare coal slurry with a mass fraction of 20-80%, and grind it into fine powder; the preparation steps of coal slurry are: first crush the coal powder to the target size, mix it with water to prepare coal slurry, and place the coal slurry in a ball mill for grinding and fine crushing. After fine crushing, the coal powder size is 0.8-80μm.

[0030] Step 2: Add a surfactant to the coal slurry obtained in step 1 to disperse it. The surfactant may be an anionic surfactant, preferably one or a mixture of alkylbenzene sulfonic acid, ammonium salt, naphthalene sulfonate, lignin sulfonate, more preferably sodium lignin sulfonate, and the amount of the surfactant added is 0.01-1% of the mass of the coal slurry obtained in step 1.

[0031] Step 3, adding iron salt and ammonia water in sequence to the coal slurry dispersed in step 2 to obtain a first mixed solution; the concentration of the iron salt solution is 10-30wt%, and the concentration of the ammonia solution is 10-30wt%; the iron salt solution and ammonia water are fed in a mass ratio of 3-6:1; preferably, the iron salt in the above-mentioned iron salt solution is a mixture of one or more of divalent sulfate, trivalent sulfate, and nitrate.

[0032] Step 4: Blow oxygen into the first mixed solution, wait for a period of time, and then add a solution of non-ferrous metal salts to obtain a second mixed solution; the non-ferrous metal salts are one or a mixture of sulfates, nitrates, and ammonium salts of molybdenum, nickel, and tungsten, and the amount of non-ferrous metal salt added is 1 to 5% of the mass of the iron salt; the volume ratio of oxygen to the coal slurry in the first mixed solution is 500 to 1000:1, and the time for blowing oxygen is ≥30 minutes.

[0033] Step 5: Filter the second mixed solution, collect the solid and dry it. In the present invention, the drying is preferably carried out by hot air drying, the drying temperature is 100-180°C, the mass content of water in the catalyst obtained after drying is less than 2%, and the catalyst can be simply crushed by a ball mill or a stirred mill to obtain a finished catalyst, and the grinding medium is a stainless steel ball.

[0034] The present invention is described in detail below with reference to specific embodiments.

[0035] Embodiment 1:

[0036] Coal A from the Hami region with an inert group content of 1.2% was selected, and a coal slurry mass fraction of 50% was prepared, and the mixture was ground in a ball mill to a size of 10 μm; then, sodium lignin sulfonate with a mass fraction of 0.05% of the coal slurry was added thereto, and the mixture was dispersed by mechanical stirring for 30 minutes; then, 20wt% of ferrous sulfate and 10wt% of ammonia solution were added to the dispersed coal slurry, and the mass ratio of ferrous sulfate solution to ammonia solution was 3:1; oxygen was blown into the obtained first mixed solution, and the volume ratio of oxygen to coal slurry was 800:1; after 30 minutes, ammonium molybdate was added in an amount of 2% of the mass of the iron salt, filtered, and dried with hot air at 120°C, and the water content of the catalyst was 4.5wt%.

[0037] The effect of the catalyst prepared in this embodiment was verified, and the specific steps were as follows: the coal in this embodiment was subjected to an autoclave experiment to verify the catalyst effect, and the reaction was carried out for 120 minutes at a reaction temperature of 450°C and a reaction pressure of 15 MPa. The liquid and solid products of the autoclave experiment were analyzed, and the effects of the catalyst in this embodiment and the industrial catalyst in the prior art were compared, as shown in Table 1.

[0038] Table 1 Comparison of mild liquefaction effect of coal A in Hami area

[0039] Conversion rate Oil yield Industrial Catalysts 90.22% 52.19% Example 1 Catalyst 96.38% 57.27%

[0040] It can be seen from Table 1 that under mild liquefaction conditions at a reaction temperature of 450°C and a reaction pressure of 15 MPa, the conversion rate of the catalyst prepared in this embodiment is significantly improved by 6.16 percentage points, and the oil yield is improved by 5.08 percentage points compared with the existing industrial catalyst. This shows that after using the catalyst of this embodiment, Hami coal A has a good liquefaction effect under mild liquefaction conditions at a low reaction pressure.

[0041] Embodiment 2:

[0042] Coal B from the Hami region with an inert group content of 0.8% was selected, and a coal slurry mass fraction of 30% was prepared, and the mixture was ground in a ball mill to a size of 2 μm; then sodium lignin sulfonate with a mass fraction of 0.02% of the coal slurry was added thereto, and the mixture was dispersed by mechanical stirring for 30 minutes; then 15wt% of ferrous sulfate and 10wt% of ammonia solution were added to the dispersed coal slurry, and the ratio of ferrous sulfate solution to ammonia solution was 4:1; oxygen was blown into the obtained first mixed solution, and the volume ratio of oxygen to coal slurry was 900:1. After 30 minutes, ammonium molybdate was added in an amount of 3% of the mass of the iron salt, filtered, and dried with hot air at 150°C, and the water content of the catalyst was 3.8wt%.

[0043] The effect of the catalyst prepared in this example was verified, and the specific steps were as follows: the coal in this example was subjected to an autoclave experiment to verify the catalyst effect, and the reaction was carried out for 120 minutes at a reaction temperature of 420°C and a reaction pressure of 16 MPa. The liquid and solid products of the autoclave experiment were analyzed, and the catalyst of this example was compared with the industrial catalyst, as shown in Table 2.

[0044] Table 2 Comparison of mild liquefaction effect of coal B in Hami area

[0045] Conversion rate Oil yield Industrial Catalysts 85.96% 43.83% Example 2 Catalyst 93.74% 50.04%

[0046] It can be seen from Table 2 that under mild liquefaction conditions of reaction temperature 420°C and reaction pressure 16MPa, the conversion rate of the catalyst prepared in this embodiment is significantly improved by 7.78 percentage points, and the oil yield is increased by 6.21 percentage points compared with the existing industrial catalyst. This shows that after using the catalyst of the embodiment, under mild liquefaction conditions of low reaction temperature and low reaction pressure, the liquefaction effect of Hami coal B is significantly improved.

[0047] Embodiment 3:

[0048] Coal C from the Hami region with an inert group content of 3.5% was selected, and a coal slurry mass fraction of 20% was prepared, and the mixture was ground in a ball mill to a size of 80 μm; then 1-naphthalenesulfonic acid sodium salt of 0.01% by mass of the coal slurry was added thereto, and the mixture was dispersed by mechanical stirring for 30 minutes; then 30wt% of ferrous sulfate and 20wt% of ammonia solution were added to the dispersed coal slurry, and the ratio of ferrous sulfate solution to ammonia solution was 5:1; oxygen was blown into the obtained first mixed solution, and the volume ratio of oxygen to coal slurry was 500:1; after 30 minutes, ammonium molybdate was added in an amount of 1% of the mass of the iron salt, filtered, and dried with hot air at 100°C to obtain a catalyst with a water content of 4.2wt%.

[0049] The effect of the catalyst prepared in this example was verified, and the specific steps were as follows:

[0050] The coal in this example was subjected to an autoclave experiment to verify the catalyst effect. The reaction was carried out for 120 minutes at a reaction temperature of 420°C and a reaction pressure of 18 MPa. The liquid and solid products of the autoclave experiment were analyzed to compare the catalyst in this example with the industrial catalyst, as shown in Table 3.

[0051] Table 3 Comparison of mild liquefaction effect of coal C in Hami area

[0052] Conversion rate Oil yield Industrial Catalysts 86.30% 45.03% Example 3 Catalyst 94.86% 51.61%

[0053] It can be seen from Table 3 that under mild liquefaction conditions of reaction temperature 420°C and reaction pressure 18MPa, the conversion rate of the catalyst prepared in this embodiment is significantly improved by 8.56 percentage points, and the oil yield is increased by 6.58 percentage points compared with the existing industrial catalyst. This shows that after using the catalyst of the embodiment, under mild liquefaction conditions of low reaction temperature and low reaction pressure, the liquefaction effect of Hami coal C is significantly improved.

[0054] Embodiment 4:

[0055] Coal D from the Hami region with an inert group content of 1.8% was selected, and a coal slurry mass fraction of 80% was prepared, and the coal was ground in a ball mill to a size of 5 μm; then, alkylbenzene sulfonic acid of 0.1% by mass of the coal slurry was added thereto, and mechanical stirring was performed for 30 minutes to disperse; then, 20wt% of ferrous sulfate and 10wt% of ammonia solution were added to the dispersed coal slurry, and the ratio of ferrous sulfate solution to ammonia solution was 3:1; oxygen was blown into the obtained first mixed solution, and the volume ratio of oxygen to coal slurry was 1000:1; after 30 minutes, ammonium molybdate was added in an amount of 5% of the mass of the iron salt, filtered, and dried with 180°C hot air to obtain a catalyst with a water content of 4.1wt%.

[0056] The effect of the catalyst prepared in this example was verified, and the specific steps were as follows:

[0057] The coal in this example was subjected to an autoclave experiment to verify the catalyst effect. The reaction was carried out for 120 minutes at a reaction temperature of 440°C and a reaction pressure of 14 MPa. The liquid and solid products of the autoclave experiment were analyzed to compare the catalyst in this example with the industrial catalyst, as shown in Table 4.

[0058] Table 4 Comparison of mild liquefaction effect of coal D in Hami area

[0059] Conversion rate Oil yield Industrial Catalysts 89.16% 44.03% Example 4 Catalyst 95.62% 52.43%

[0060] It can be seen from Table 4 that under mild liquefaction conditions of reaction temperature 440°C and reaction pressure 14MPa, the conversion rate of the catalyst prepared in this embodiment is significantly improved by 6.46 percentage points, and the oil yield is increased by 8.40 percentage points compared with the existing industrial catalyst, indicating that after using the catalyst of the embodiment, under mild liquefaction conditions of low reaction temperature and low reaction pressure, the liquefaction effect of Hami coal D is significantly improved.

[0061] Under the guidance of the above-mentioned Examples 1 to 4, those skilled in the art may also use other anionic surfactants such as naphthalenesulfonates and ammonium salts.

[0062] In the description of this application, words such as "first" and "second" are only used to distinguish different objects, and do not limit the quantity and execution order, and words such as "first" and "second" do not necessarily limit differences. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0063] Parts not described in the present invention can be implemented by those skilled in the art by referring to the existing technology.

[0064] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present application and are not intended to be limiting of the present application. As long as they are within the spirit of the present application, appropriate changes and modifications to the above embodiments should fall within the scope of protection of the claims of the present application.

Claims

1. A method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area, wherein the inert group of the coal in Hami area accounts for less than 2%. It is characterized in that The preparation method comprises the following steps: (1) Prepare a coal slurry with a certain mass fraction and grind it into fine powder; (2) adding a surfactant to the coal slurry obtained in step (1) to disperse it; (3) adding iron salt and ammonia water to the coal slurry dispersed in step (2) in sequence to obtain a first mixed solution; (4) blowing oxygen into the first mixed solution, and after a period of time, adding a solution of a non-ferrous metal salt to obtain a second mixed solution; (5) Filter the second mixed solution, collect the solid and dry it to obtain the product.

2. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 1, It is characterized in that In step (1), the coal powder is crushed and mixed with water to prepare coal slurry, the mass fraction of the coal slurry is 20-80%; and the coal powder is ground in a ball mill to a size of 0.8-80 μm.

3. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 1, It is characterized in that In step (2), the surfactant is an anionic surfactant, and the anionic surfactant is one or a mixture of several of alkylbenzene sulfonic acid, ammonium salt, naphthalene sulfonate, and lignin sulfonate.

4. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 3, Features: In step (2), the surfactant is sodium lignin sulfonate, and the amount of sodium lignin sulfonate added is 0.01-1% of the mass of the coal slurry obtained in step (1).

5. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 1, Features: In step (3), the concentration of the iron salt solution is 10-30wt%, and the concentration of the ammonia solution is 10-30wt%; the iron salt solution and the ammonia solution are fed in a mass ratio of 3-6:

1.

6. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 5, Features: The iron salt in the iron salt solution is one of divalent sulfate, trivalent sulfate and nitrate or a mixture of several of them.

7. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 1, Features: In step (4), the non-ferrous metal salt is one or a mixture of sulfates, nitrates and ammonium salts of molybdenum, nickel and tungsten.

8. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 7, Features: The amount of the non-ferrous metal salt added is 1-5% of the mass of the iron salt; the volume ratio of oxygen to the coal slurry in the first mixed liquid is 500-1000:1, and the time of blowing oxygen is ≥30 minutes.

9. The method for preparing a direct coal liquefaction catalyst suitable for mild liquefaction of coal in Hami area according to claim 1, Features: In step (5), the drying temperature is 100-180° C., and the mass content of water in the catalyst obtained after drying is less than 2%.

10. A coal direct liquefaction catalyst suitable for mild liquefaction of coal in Hami area, It is characterized in that The compound is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of coal-loaded high-activity iron-based catalyst and application of coal-loaded high-activity iron-based catalyst in coal direct liquefaction

    CN122875222A